Evaluation on compression properties of different shape and perforated rHDPE in concrete structures - Yaakob, Mohd Yuhazri; K. M., Hafiz; Y. Z. A., Myia; Jia, C. P.; Sihombing, Haeryip; Salit, Mohd Sapuan; Badarulzaman, Nur Azam (Institute Of Physics (IOP) Publishing, 2017)
The purpose of this study was to develop a concrete structure by incorporating waste HDPE plastic as the main reinforcement material and cement as the matrix via standard casting technique. There are eight different shapes of rHDPE reinforcing structure were used to investigate the compression properties of produced concrete composites. Experimental result shown that the highest shape in compressive strength of rHDPE reinforcing structure were the concrete with the addition of X-perforated beam (18.22 MPa), followed by X-beam (17.7 MPa), square perforated tube (17.54 MPa), round tube (17.42 MPa) and round perforated tube (16.69 MPa). In terms of their compressive behavior, the average concrete containing rHDPE reinforcement was successfully improved by 6 % of the mechanical characteristic compared to control concrete. It is shown that the addition of waste plastic as reinforcement structure can provide better compressive strength based on their shape and pattern respectively.